"mTOR Signaling Pathway": A Potential Target of Curcumin in the Treatment of Spinal Cord Injury. (12th June 2017) - Lin, Jingquan; Huo, Xue; Liu, Xuehong
Abstract : The purpose of this review is to discuss the possibility of the treatment of spinal cord injury (SCI) with curcumin via regulating the mTOR signaling pathway, which may provide another strong support for curcumin to be a promising medicine applied to the treatment of SCI. Curcumin is termed as a multifunctional targeting therapy drug that regulates the mTOR signaling pathway in the treatment of numerous diseases. Previous research has already revealed that mTOR signaling pathway plays a vital role in prognosis, which involves the axon regeneration and autophagy. This review discusses a potential mechanism that curcumin suppresses the activation of this pathway and ameliorates the microenvironment of axons regeneration which would provide a new way that induces autophagy appropriately.